The post-80s generation: exploring the attitudes toward family and housing. (2nd July 2020) - Xian, Shi; Forrest, Ray
ABSTRACT: Previous literature has paid attention to housing pathways and cohort features of young people, but studies connecting the two themes are lacking. This paper offers a perspective on the cohort analysis of young people based on their housing choices and aspirations. With empirical evidence from a two-round social survey, this study explores the 'not leaving home' pattern of the housing choices of young people in Hong Kong. With some supplementary subgroup analysis, the cohort label of a 'post-80s generation' in Hong Kong is challenged. Contradictions are revealed in the views of our young people about housing and family life, and further analysis is conducted to examine the impacts of economic and sociocultural factors in the local context of Hong Kong. This study argues that we need to look beyond the shared features and subgroup differences and consider how sociocultural factors, particularly gender, marriage, education, and social norms, interact with economic factors to shape housing choices, aspirations and apparent contradictions in the viewpoints of young people regarding their personal development and housing futures. In doing so, the paper also engages with debates around intra and intergenerational dynamics and inequalities. The paper focuses on Hong Kong but these debates have international resonance.